If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -6 = 7x Reorder the terms: -6 + 10x = 7x Solving -6 + 10x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -6 + 10x + -7x = 7x + -7x Combine like terms: 10x + -7x = 3x -6 + 3x = 7x + -7x Combine like terms: 7x + -7x = 0 -6 + 3x = 0 Add '6' to each side of the equation. -6 + 6 + 3x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = 0 + 6 3x = 0 + 6 Combine like terms: 0 + 6 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| y+(-10)=36 | | 8y+1=2y-26 | | .5f+10=48 | | 6(2x+3)+2= | | (16x-3)(2)=0 | | 8p+9p=34 | | a-6-7a=1-6a | | 11c-4-3=8 | | (16x-3)(8)=0 | | 1/3x-1/6y=1 | | -4/5a=12/17 | | 2x-6=8-2x | | 3=2y | | 16x+3=47 | | 4+17/-2=0 | | 8(2a-8)=-4(-3a+6) | | 2c+c+12=14 | | 1/2f+10=48 | | 33/d=12 | | z/14=-28 | | 1-2x=-9+8x | | 8x+4x+2=12x+2 | | 87=(2x+7) | | x^2+3x+14=47.75 | | (15)t+(9)=15t+9 | | d/12=33 | | -20=7 | | 5-5n=-55 | | 8a+10a= | | 16/1/4=x | | 32-(-86)= | | 5x+8-1x=20+4x-12 |